Nonsequential Response in Mountainous Areas of Southwest China - Liu, Lin; Ye, Sheng; Chen, Cangyi; Pan, Hailong; Ran, Qihua (Frontiers in Earth Science, 2021)
Non-sequential response is the phenomenon that the change of soil water content at the lower layer is larger than that of the upper layer within a set time interval. It is often ignored due to the lack of spatial distributed measurements at watershed scale, especially in mountainous area where extensive monitoring network is expensive and difficult to deploy. In this study, the subsurface non-sequential response in a mountainous watershed in Southwest China was investigated by combining field monitoring and numerical simulation. A physics-based numerical model (InHM) was employed to simulate the soil water movement to explore the occurrence of the subsurface non-sequential response. The topographic wetness index (TWI = ln(a/tan b)) was used to distinguish the topographic zone corresponding to the non-sequential response at different depths. The non-sequential response mainly came from the subsurface lateral flow initiated at the soil-bedrock interface or at relatively impermeable layer. The results showed that the occurrence depth of the non-sequential response increased with precipitation intensity when the time since last event was more than 24 hours and the total amount of this event exceeded 37 mm. During a rainfall event, the non-sequential response occurred at the middle layer in the hillslope zone and the deep soil layer beneath the channel. In case of rainfall event with two peaks, the region observed with non-sequential response expanded. The soil layer at the interface of bedrock could be saturated quickly, and became saturated upwards. This kind of non-sequential response can be observed on the hillslope at the beginning of rainfall events, and then found beneath stream channels afterwards. Furthermore, non-sequential response could also happen after rainfall events. The results improved our understanding of non-sequential response and provided a scientific basis for flash flood research in mountainous areas.